The Relationship of Venous Diameter to Reflux, Cephalad Thrombus and Cephalad Reflux Following Deep Venous Thrombosis - Tullis, M J; Meissner, M H; Bergelin, R O; Caps, M T; Manzo, R A; Strandness, D E (Thrombosis and Haemostasis, 1997)
Duplex ultrasonography was used to measure the diameters of the common femoral, superficial femoral and popliteal vein segments in 123 patients following DVT. A cross sectional analysis was done based on the most recent visit to determine chronic venous diameter changes following DVT.Venous diameters in recanalized segments were smaller at all levels compared to those never occluded (p = 0.06 for CFV and p <0.05 for SFV and PV). After accounting for a previous history of occlusion, the diameters of the segments with and without reflux were not significantly different. There was also no evidence of venodilation in segments caudal to cephalad reflux or thrombus.Recanalized veins are smaller in diameter than those which were never thrombosed. Cephalad thrombus or reflux is not associated with venodilatation of caudal segments. Reflux following DVT is probably secondary to valvular damage rather than hypertension, since there was no diameter difference between refluxing and non-refluxing segments.